THE CONCEPT OF PROFESSIONAL DEVELOPMENT IN THE WORLD OF WORK: KONSEP PERKEMBANGAN PROFESIONAL DALAM DUNIA KERJA - Lafau , Niati; Darmansari Lahagu, Weni (LPPM UPMI, 2023)
In the world of work, the word professional is heard quite often. Someone who works professionally is someone who can work and complete their affairs effectively and efficiently. Generally, a professional person tends to have a positive image in the eyes of his superiors and those around him. Professionalism, a term often heard in the world of work, indicates high standards in how someone carries out their duties and responsibilities. A professional is an individual who dedicates himself to pursuing his expertise in a particular field, carries out tasks with unmatched precision and quality, and shows high commitment to his work. It is important to remember that professionalism is not just about technical proficiency in a field of work, but also includes personal qualities that influence interactions and relationships with others in the workplace. In the world of work, a professional attitude is a mandatory requirement for every employee. Labor law in Indonesia is regulated in Law no. 13 of 2003 concerning Employment. Labor law regulates all matters relating to labor before, during and after workAccording to the Big Indonesian Dictionary (KBBI), the meaning of the word professionalism is quality, quality and behavior which are characteristics of a profession or a professional person. Professionalism itself is taken from the basic word